An intact cysteine-rich domain is required for dystrophin function. - Bies, R D (1992)
The carboxyl terminus of dystrophin is encoded by a highly conserved, alternatively spliced region of the gene. The few rare mutations reported in this region are of interest in unraveling the function of the dystrophin molecule. An unusual case of infantile onset Duchenne muscular dystrophy (DMD) with an internal 3' genomic deletion, and a membrane localized non-functional dystrophin protein, was used to explore the functional activity of this region. The patient's cDNA sequence showed an intragenic 1824-bp deletion precisely excising the cysteine rich and alternatively spliced COOH-terminal domains of dystrophin. The unaltered final 2.7 kb of the patients transcript was defined as a single exon localized to two genomic fragments, with the 5.9 kb HindIII fragment containing the stop codon. To understand the significance of deletions in this important region of the dystrophin gene, we mapped the order and cDNA coordinates for the 3' genomic HindIII fragments encoding the cysteine rich and alternative splicing domains. This 3' gene map was used to compare the clinical phenotype of the other reported COOH-terminal deletions in the literature. Our analysis concludes that the cysteine-rich domain confers an important function for the dystrophin protein.